Analysis of contact and bending stiffness for Curvic couplings considering contact angle and surface roughness. (December 2019) - Yu, Younghun; Lee, Bora; Cho, Yongjoo
This paper develops a method for calculating the contact and bending stiffness of a Curvic coupling, and investigates stiffness changes according to the coupling shape and surface roughness characteristics. The surface of the on-site Curvic coupling is chosen as reference for a most accurate simulation. The three parameters representing the surface roughness characteristics—the standard deviation of the asperity height distribution, the average radius of asperities, and the density of asperity on the nominal contact area—are calculated with a profile of the coupling surface through a random process: the contact problem between rough surfaces is tackled using the Greenwood-Williamson model, the Curvic coupling is modeled assuming that it has as many teeth as possible within the machining limits depending on the contact angle, and the tangential stiffness resulting from the contact angle is calculated by dividing into the stick and slip regions, and is taken into account in terms of total stiffness. With this, results showed that using Curvic couplings reduces stiffness than using flat disc couplings because of the contact angle, and that the standard deviation of rough surface height is the most crucial surface parameter affecting stiffness.